2018
DOI: 10.1038/s41467-018-03878-6
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the adsorption process in ZIF-8 using high pressure crystallography and computational modelling

Abstract: Some porous crystalline solids change their structure upon guest inclusion. Unlocking the potential of these solids for a wide variety of applications requires full characterisation of the response to adsorption and the underlying framework–guest interactions. Here, we introduce an approach to understanding gas uptake in porous metal-organic frameworks (MOFs) by loading liquefied gases at GPa pressures inside the Zn-based framework ZIF-8. An integrated experimental and computational study using high-pressure c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
196
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(214 citation statements)
references
References 54 publications
16
196
1
1
Order By: Relevance
“…ZIF‐8 is composed by Zn 2+ ions tetrahedrally coordinated by four imidazolate rings with unit formula Zn 6 (mIm) 12 (mIm=2‐methylimidazolate). The structure contains one central nanopore per unit cell, with 2500 Å 3 volume and 11.6 Å pore diameter . ZIF MOF series containing imidazole based linkers has been widely used in different fields due to their robust structure, resistance to thermal changes and chemical stability .…”
Section: Resultsmentioning
confidence: 99%
“…ZIF‐8 is composed by Zn 2+ ions tetrahedrally coordinated by four imidazolate rings with unit formula Zn 6 (mIm) 12 (mIm=2‐methylimidazolate). The structure contains one central nanopore per unit cell, with 2500 Å 3 volume and 11.6 Å pore diameter . ZIF MOF series containing imidazole based linkers has been widely used in different fields due to their robust structure, resistance to thermal changes and chemical stability .…”
Section: Resultsmentioning
confidence: 99%
“…19 In recent years, a number of studies, both experimental and theoretical, have been performed to study the role of pressure, temperature, and the nature of the gas molecules on the adsorption capacity of ZIF-8, including the apparently counterintuitive case of an increased pore window size upon pressure. [20][21][22][23][24][25] More specifically, using both in situ powder X-ray diffraction and molecular simulation, it has been shown that a "gate-opening" or "swing-effect" adsorption-induced structural change occurs in ZIF-8 at much lower pressures, where -similar to the 1.47 GPa phase described above -the imidazolate linkers rotate so as to increase the size of the accessible pore window. 21,26,27 These classes of motions, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The other converted material is ZIF‐8, which is a typical metal‐organic framework (MOF) with a porous 3D zeolite crystal structure. ZIF‐8 has been studied extensively and shows a great potential in catalysis, gas adsorption, and optics ,. Herein, solvothermal reaction was employed to convert the ZnO NWs into ZIF‐8 structures on the 3D Si substrate.…”
Section: Resultsmentioning
confidence: 99%